Salmonella in Poultry; An Overview - Sania Tariq; Abdul Samad; Muhammad Hamza; Areeb Ahmer; Ayesha Muazzam; Shehroz Ahmad; Abdelslam Masoud Abobakr Amhabj (International Journal of Multidisciplinary Sciences and Arts, 2022)
An essential part of commercial poultry production is safeguarding flocks of birds against contamination by unwanted microorganisms. Currently, a serious issue called salmonellosis poses a threat to the chicken industry globally. The two most virulent serovars in avian species, Salmonella gallinarium and Salmonella pullorum (Fowl Typhoid) cause systemic infection and significant financial losses in the poultry sector. Salmonella nontyphoidal serotypes (Paratyphoid illness) pose a risk to the public's health because of their role in cases of food poisoning and their significance as zoonotic agents. All animals, including humans, can transmit the intestinal bacterium known as salmonella. Out of a total of 2500 serovars, Salmonella pullorum (pullorum illness) and S. gallinarum (bird typhoid) are the two host-adapted serovars that primarily harm poultry. Salmonella can spread horizontally from contaminated environments to birds as well as vertically from parent flocks to offspring. The danger of the introduction and persistence of infections can be substantially reduced by good management of biosecurity. This study is an overview of Salmonella in poultry which tell us some diagnostic and treatment of salmonella. By reading this study people will get sound knowledge regarding salmonella even they will be able to do desirable management in order to save their birds from Salmonella.